Effectiveness of Archive Management of Disbursement Orders in the Treasury Sector of the Regional Financial Management Agency South Sulawesi Province - Rosdiana Rosdiana; St. Rahmiyah Saleh; Nurwinda Nurwinda (Universitas Negeri Makassar, 2021)
Effectiveness of Management of Funds Disbursement Order (SP2D) Archives are activities carried out starting from planning, preparation and implementation through the Funds Disbursement Warrant (SP2D) procedure to achieve a goal effectively and efficiently. This research is a quantitative descriptive study which aims to determine the Effectiveness of the Management of Fund Disbursement Order Archives (SP2D). The population of this study were 23 employees. Data collection techniques used are observation, questionnaires, interviews and documentation. Then the data analysis in this research is descriptive analysis technique. The effectiveness of SP2D archive management in the treasury field is categorized as quite effective because of inadequate archive equipment and equipment, archive rescue that still receives less attention due to inadequate archive storage space, and archive shrinkage that is not carried out regularly, causing the accumulation of archives in each section and in the archives of the Regional Financial Management Agency.